2016
DOI: 10.1007/s10792-016-0262-z
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for treatment outcomes after corneal crosslinking for keratoconus: a validation study

Abstract: Previous research suggested that baseline corrected distance visual acuity (CDVA) and maximum keratometry (Kmax) are the predictors for effectiveness of corneal crosslinking (CXL) for keratoconus. The aim of this study was to validate the previously determined predictors in a new treatment cohort. A prospective cohort of 112 eyes in 90 consecutive patients was used to validate the results of 102 eyes in 79 patients from our previous prospective cohort. All patients were treated using epithelium-off corneal CXL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
29
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 30 publications
5
29
1
Order By: Relevance
“…In addition, unlike the findings in their first cohort, in the validation study they found that younger patients had significantly better results with respect to visual acuity 108,110. Soeters et al113 had also identified age as a prognostic factor 110…”
Section: Patient Selectionmentioning
confidence: 73%
See 3 more Smart Citations
“…In addition, unlike the findings in their first cohort, in the validation study they found that younger patients had significantly better results with respect to visual acuity 108,110. Soeters et al113 had also identified age as a prognostic factor 110…”
Section: Patient Selectionmentioning
confidence: 73%
“…Godefrooij et al110 identified possible predictors for results of the effect of CXL in a prospective cohort, and recently in a different prospective cohort they performed a validation study 108. They found by using univariate analysis that a predictor of higher improvement in K max was male sex, while atopia was a predictor of a slight (but significant) decrease in improvement in visual acuity 108.…”
Section: Patient Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Keratoconus patients with a minimal corneal thickness of 400 μm were offered CXL in case of confirmed disease progression. Keratoconus progression was defined as consistent change in at least one of the two following parameters during the previous 12 months: an increase in the steepest keratometry value (Kmax) of ≥1 D [8][9][10][11][12] and/or a decrease in minimal corneal thickness of ≥10 μm [13,14].…”
Section: Patientsmentioning
confidence: 99%